Keamanan Informasi Menggunakan iso27002 Pada Data Organisasi Paskibra Kopral15 di SMPN 15 Medan - Miftahul Jannah; Nurhayati Nurhayati; Adhe Eva Yolanda; Ali Ikhwan (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2023)
The type of audit used in this study is an internal audit using the Iso 27002 information security standard. KOPRAL or Garuda Lima Belas Soldier Command is an Extracurricular Paskibra in SMP N 15 Medan, this extracurricular is quite popular with many existing students, the initial purpose of its formation This Paskibra is to raise the red and white flag on national days, such as independence, youth oath, and teacher's day, currently KOPRAL has 29 batches.